2003
DOI: 10.1136/jech.57.5.361
|View full text |Cite
|
Sign up to set email alerts
|

Social inequalities in depressive symptoms and physical functioning in the Whitehall II study: exploring a common cause explanation

Abstract: Study objective: This study investigated which risk factors might explain social inequalities in both depressive symptoms and physical functioning and whether a common set of risk factors might account for the association between depressive symptoms and physical functioning. Design: A longitudinal prospective occupational cohort study of female and male civil servants relating risk factors at baseline (phase 1: 1985-8) to employment grade gradients in depressive symptoms and physical functioning at follow up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
124
5
2

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(144 citation statements)
references
References 34 publications
13
124
5
2
Order By: Relevance
“…Yet, the scale was reliable, it was factorially derived from a validated questionnaire within the Whitehall II study (Stansfeld, Marmot, 1992) and is composed of four of the seven items of a validated severe depression subscale, and has been used in previous publications. (Stansfeld et al, 2003;Nicholson et al, 2005) We did not find a consistent cross-sectional relationship between high levels of inflammation and depressive symptoms. It is possible that the cognitive symptoms of depression we measured are not associated in the same way with inflammation as measures of depression which include neurovegetative symptoms which might more readily be expected to be associated with inflammation.…”
Section: Methodological Considerationsmentioning
confidence: 41%
See 2 more Smart Citations
“…Yet, the scale was reliable, it was factorially derived from a validated questionnaire within the Whitehall II study (Stansfeld, Marmot, 1992) and is composed of four of the seven items of a validated severe depression subscale, and has been used in previous publications. (Stansfeld et al, 2003;Nicholson et al, 2005) We did not find a consistent cross-sectional relationship between high levels of inflammation and depressive symptoms. It is possible that the cognitive symptoms of depression we measured are not associated in the same way with inflammation as measures of depression which include neurovegetative symptoms which might more readily be expected to be associated with inflammation.…”
Section: Methodological Considerationsmentioning
confidence: 41%
“…This has been validated within the Whitehall II study, (Stansfeld, Marmot, 1992) based on principal components factor analysis (Nicholson et al, 2005) and compared with the seven-item severe depression subscale from the GHQ-28. (Stansfeld et al, 2003) The items requested whether, compared to a usual state, the participant has recently: been thinking of yourself as a worthless person; felt that life is entirely hopeless; felt that life isn't worth living; and, found at times you couldn't do anything because nerves were too bad. These items assess cognitively-based symptoms of depression only.…”
Section: Cognitive Symptoms Of Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can also examine the extent to which well-being is affected by gender, health status, age and the presence of children. Many studies have found that socio-demographic factors play an important role in explaining inter-individual variability in well-being 14,15,16 and depressive symptoms 17,18 , as well as in physical morbidity 19,20,21,22 .…”
Section: Socio-demographic Factors and Labour Market Characteristicsmentioning
confidence: 99%
“…The association between mental health problems and unemployment, as well as atypical and temporary employment has been observed in studies carried out in Brazil 28 and elsewhere 7,25,27 . In one study among English civil servants, employment characteristics were the most influential factors in the inverse gradient between "employment grade" and depressive symptoms 29 . Unemployment and job insecurity are considered to have a negative influence on mental health not only on account of the financial implications, but also due to the psychosocial aspects such as the breakdown of an individual's time structure, a lack of future perspectives, lower self-esteem and dissatisfaction with the working situation 30 .…”
Section: Labor Market Status and Healthmentioning
confidence: 99%